Feline Stool-Associated Circular DNA Virus (FeSCV) in Diarrheic Cats in China - Hao, Xiangqi; Li, Yanchao; Hu, Xinkai; Fu, Xueying; Dong, Jie; Zhang, Haoyang; Zhou, Pei; Li, Shoujun (Frontiers in Veterinary Science, 2021)
Feline stool-associated circular DNA virus (FeSCV) is an unclassified circular replication-associated protein-encoding single-stranded (CRESS) DNA virus that was discovered in cats in Japan in 2018. Few studies on the genomic characteristics and prevalence of FeSCV have been conducted. To investigate whether FeSCV has been circulating in domestic cats in Guangdong, China, fecal samples were collected from cats with diarrhea in an animal hospital in 2018 to promote research on FeSCV. The FeSCV genome was obtained by PCR amplification and sequencing, and the detected virus was named PY4 (GenBank No. MT732515). The genome of PY4 was 2034 nt in size, which was 12 nt smaller than the reported genome of Japanese FeSCV strains (KU7, KU8, KU9, KU14) (2046 nt). The PY4 strain shared 95.1% ~ 95.5% homology with Japanese FeSCV strains. Notably, the Cap protein of PY4 was mutated at 15 amino acid sites, and the PY4 genome contained a unique open reading frame 3. In addition, there were two additional base insertions in the stem-loop structure of PY4, and the nucleotide homology of the spacer region was not high. A phylogenetic tree based on Rep proteins showed that PY4, Japanese FeSCVs and rodent stool-associated circular viruses (RodSCVs) clustered together, suggesting that they might share a similar origin in their phylogenetic evolution. In this study, samples collected in Guangzhou, China, in 2018 were subjected to an etiological investigation, and 20% (2/10) of the samples were positive for FeSCV. The ORFs, stem-loop structures, Cap proteins and intergenic region sequences of PY4 were significantly different from those reported in Japan. This is the first report of FeSCV in domestic cats with diarrhea in China, and further epidemiological studies are urgently needed to assess the impact of the virus on cats.